Two Case Presentations Infected by Trichosporon asahii and Treated with Voriconazole Successfully - Hikmet Gulsah Tanyildiz; Sule Yesil; Sule Toprak; Mehmet Onur Candir; Gurses Sahin (Case Reports in Infectious Diseases)
Background. Trichosporon asahii is an opportunistic fungus that causes infections in immunosuppressed patients. Neutropenia developing due to malignancies is an important risk factor for fungal infection. Case Report. We present two pediatric oncology cases successfully treated with voriconazole after T. asahii infection that is known to cause fatal sepsis and invasive fungal infection. Conclusion. There is no conclusive evidence that the antifungal agent voriconazole is effective in the neutropenic patients infected with Trichosporon asahii. Liposomal amphotericin B has also been reported to be inadequate for treatment. We believe that our patients were successfully treated and survived because the antifungal agents were started early and properly, although the infection can be fatal in up to 80% of cases despite treatment.